2016
DOI: 10.1016/j.jpowsour.2016.04.076
|View full text |Cite
|
Sign up to set email alerts
|

4D analysis of the microstructural evolution of Si-based electrodes during lithiation: Time-lapse X-ray imaging and digital volume correlation

Abstract: Silicon is a promising candidate to substitute or complement graphite as anode material in Li-ion batteries due, mainly, to its high energy density. However, the lithiation/delithiation processes of silicon particles are inherently related to drastic volume changes which, within a battery's physically constrained case, can induce significant deformation of the fundamental components of the battery that can eventually cause it to fail. In this work, we use non-destructive time-lapse X-ray imaging techniques to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 27 publications
(35 reference statements)
3
41
0
1
Order By: Relevance
“…Many experimental and theoretical studies have been devoted to this aspect on Si electrodes. In situ X-ray imaging experiments have confirmed this behavior, [16] largely inferred previously from in situ X-Ray Diffraction experiments. [13][14][15] It was shown that for both crystalline and amorphous silicon, the first lithiation proceeds via the coexistence of two phases separated by a sharp interface: a heavily lithiated phase progressively invades the active material which remains practically unaffected away from the interface.…”
Section: Doi: 101002/aenm201702568supporting
confidence: 78%
“…Many experimental and theoretical studies have been devoted to this aspect on Si electrodes. In situ X-ray imaging experiments have confirmed this behavior, [16] largely inferred previously from in situ X-Ray Diffraction experiments. [13][14][15] It was shown that for both crystalline and amorphous silicon, the first lithiation proceeds via the coexistence of two phases separated by a sharp interface: a heavily lithiated phase progressively invades the active material which remains practically unaffected away from the interface.…”
Section: Doi: 101002/aenm201702568supporting
confidence: 78%
“…However, surprisingly, very few published studies made use of DVC to translate microstructure changes into 4D displacement (or velocity) fields. One exception though is due to one team that studied lithium batteries in operando [178,65]. In these examples, DVC could inform on the strains, and hence ageing conditions under electrochemical changes, and finally provided a clear picture of the performance loss of such batteries.…”
Section: D Kinematic Measurements From Fast Tomographymentioning
confidence: 99%
“…For cellulose fiber mats correlations between high density gradient zones and maximum eigen strains were reported [112]. More recently it was shown that the volume change in Si-based electrodes increased with the lithiation degree, while the gray levels decreased with respect to the original (i.e., nonlithiated) state [178]. Nodular graphite cast iron, which is a model material for DVC analyses, has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that microscopic heterogeneities and defects [12] within these materials may act as nucleation points for macroscopic failures and, consequently, there is a need to understand these material microstructures in greater detail [13]. For example, the expansion and contraction of active electrode materials can cause SEI and particle fracture on the micro scale [14,15], whereas the same chemo-mechanical forces can result in severe delamination and electrical isolation of the bulk electrode [5,16]. The authors and others have led work over the past 5 years in the application of X-ray tomography to explore these materials both ex-situ [14,[17][18][19][20][21] and in-situ [14,15,22,23].…”
Section: *Manuscript Text (With Figures and Captions Embedded) -Cleanmentioning
confidence: 99%
“…For example, the expansion and contraction of active electrode materials can cause SEI and particle fracture on the micro scale [14,15], whereas the same chemo-mechanical forces can result in severe delamination and electrical isolation of the bulk electrode [5,16]. The authors and others have led work over the past 5 years in the application of X-ray tomography to explore these materials both ex-situ [14,[17][18][19][20][21] and in-situ [14,15,22,23]. Additional work using tomography and radiography to characterize cell architecture during failure [22] and post mortem [24,25] as well as to understand the role of safety features [26][27][28] help to build a comprehensive understanding of the role of each component in driving device degradation and failure.…”
Section: Introductionmentioning
confidence: 99%